El asesinato del sábado por la mañana : un caso psicoanalítico - Gur, Batya (Nuevos tiempos (Madrid, Spain), 2014)
When a well-respected analyst is found dead at the Jerusalem Psychoanalytic Society headquarters, Chief Inspector Michael Ohayon is hired to infiltrate the complex society and find the killer.